A magnesium aluminum alcoholate nanowire and its preparation method and application

Magnesium-aluminum alkoxide nanowires are prepared by heating Mg-Al-Li alloy in anhydrous isopropanol, and the electron and geometric effects between metals are used to solve the harsh reaction conditions and complicated steps of the metal nanowire preparation method in the prior art. The problem of this paper achieves efficient and low-cost nanowire preparation, improving reaction efficiency and material performance.

CN116332725BActive Publication Date: 2024-12-17HARBIN INST OF TECH WEIHAI RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310060926.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-19
Publication Date
2024-12-17
Estimated Expiration
2043-01-19

AI Technical Summary

Technical Problem

The existing metal nanowire preparation methods have harsh reaction conditions, cumbersome steps and difficult operation, resulting in high production costs and low efficiency.

Method used

The Mg-Al-Li alloy is heated in anhydrous isopropanol to prepare magnesium aluminum alkoxide nanowires, and the reaction of Mg-Al alkoxide is formed into a 1D nanomaterial, which uses the electron and geometric effects between metals to improve the reaction efficiency. Shorten the reaction time.

Benefits of technology

Efficiently synthesize needle-shaped nanoscale magnesium and aluminum nanowires with high aspect ratios at room temperature or lower temperatures, simplifying operation steps, reducing production costs, and broadening the preparation direction of metal alcohol oxide nanowires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116332725B_ABST
    Figure CN116332725B_ABST
Patent Text Reader

Abstract

A magnesium aluminum alcoholate nanowire and its preparation method and application. The present invention belongs to the field of nano functional materials. The present invention aims at the technical problems that the current preparation methods of metal nanowires have harsh reaction conditions, complicated preparation steps and difficult operation. The method of the present invention is as follows: Mg-Al-Li alloy is cut into blocks, added to anhydrous isopropanol, and heated at a constant temperature of 65-75°C for 22-24h. The present invention uses Mg-Al-Li alloy as a reaction substrate, and Mg-Al reacts to form Mg 17 Al 12 The electronic effect between metals accelerates the transfer of electrons. In addition, there is a geometric effect between magnesium and aluminum alloys, which can form new active sites at the two-phase interface between magnesium and aluminum metals, thereby significantly improving the reaction efficiency and shortening the reaction time. Magnesium isopropoxide and aluminum nanowires with high aspect ratios are efficiently synthesized at room temperature or lower temperatures, broadening the direction of preparing metal alcohol oxide nanowires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano functional materials, and specifically relates to a magnesium aluminum alcoholate nanowire and a preparation method and application thereof. Background Art

[0002] One-dimensional nanomaterials, namely nanowires (NWs), can construct nanostructures of different morphologies such as nanowhiskers, nanorods, nanobelts, nanotubes, and nanofibers. One-dimensional nanomaterials, with their unique structures, offer prospects for enhancing the electrical, optical, and mechanical properties of various functional materials and composites. In recent years, one-dimensional nanomaterials have been widely used in electronics, sensors, catalysts, filters, energy storage and conversion technologies, and water treatment; therefore, one-dimensional nanomaterials have become attractive building blocks or enhancement media for the next generation of devices and materials. Usually, metal nanowires are of various types and morphologies, so their preparation methods are also different.

[0003] At present, metal nanowires are mostly prepared by physical vapor deposition, chemical vapor deposition (CVD), chemical vapor transport (CVT), gas-solid-solid (VSS), template growth, solvothermal method, etc. Although one-dimensional nanostructures are promising in improving the performance of functional materials and composite materials, these methods have harsh reaction conditions, relatively cumbersome preparation steps, and difficult operation. Therefore, it is necessary to find a method for preparing metal nanowires at room temperature and ambient pressure to greatly simplify the operation steps, reduce production costs, and optimize reaction conditions. Summary of the invention

[0004] The present invention aims to solve the technical problems of the current preparation method of metal nanowires, such as harsh reaction conditions, complicated preparation steps and difficult operation, and provides a magnesium aluminum alcoholate nanowire and a preparation method and application thereof.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a method for preparing magnesium aluminum alcoholate nanowires, wherein the preparation method is carried out according to the following steps:

[0007] The Mg-Al-Li alloy is cut into blocks, added into anhydrous isopropanol, and heated at a constant temperature of 65-75° C. for 22-24 hours to obtain magnesium aluminum alcoholate nanowires.

[0008] Further defined, the anhydrous isopropanol is treated by adding molecular sieves thereto and heating at 60-80° C. to remove traces of water.

[0009] Further defined, molecular sieves are added to anhydrous isopropanol and heated at 60-80°C for one day.

[0010] It is further defined that the mass ratio of Mg, Al and Li in the Mg-Al-Li alloy is 8:1:1.

[0011] It is further defined that the ratio of the mass of the Mg-Al-Li alloy to the volume of anhydrous isopropyl alcohol is ≤5 mg / ml.

[0012] Further defined, constant temperature heating is performed at 70°C for 24 hours.

[0013] It is further defined that the size of the Mg-Al-Li alloy block is 20 mm×20 mm×10 mm.

[0014] Further defined, the Mg-Al-Li alloy block is polished smooth and then added into anhydrous isopropanol.

[0015] The second object of the present invention is to provide a magnesium aluminum alcoholate nanowire prepared by the above method.

[0016] The third object of the present invention is to provide an application of the magnesium aluminum alcoholate nanowires prepared by the above method as a reinforcing phase of a composite material.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) The present invention uses Mg-Al-Li alloy as a reaction substrate and utilizes the minimization of stress at the boundary during the transformation of Mg alcohol and Al alcohol salt (the transformation will cause a sharp volume change of more than 600%) to promote the formation of metal alcohol oxide in the form of 1D nanomaterials (nanowires) on the surface of each grain.

[0019] (2) The present invention uses Mg-Al-Li alloy as the reaction substrate, and Mg-Al reacts to form Mg 17 Al 12 The electronic effect between metals accelerates the transfer of electrons. In addition, there is a geometric effect between magnesium and aluminum alloys, which can form new active sites at the two-phase interface between magnesium and aluminum metals, thereby significantly improving the reaction efficiency and shortening the reaction time. Needle-shaped nanoscale isopropoxide magnesium and aluminum nanowires with high aspect ratios are efficiently synthesized at room temperature or lower temperatures, broadening the direction of preparing metal alcohol oxide nanowires. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope morphology of the magnesium aluminum alcoholate nanowires prepared in Example 1;

[0021] Figure 2 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 1;

[0022] Figure 3 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 2;

[0023] Figure 4 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 3;

[0024] Figure 5 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 4;

[0025] Figure 6 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 5;

[0026] Figure 7 The scanning electron microscope morphology of the magnesium aluminum alcoholate prepared in Comparative Example 6;

[0027] Figure 8 This is the scanning electron microscope morphology of the magnesium aluminum alkoxide prepared in Comparative Example 7. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0030] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0031] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0032] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0033] Example 1: The preparation method of a magnesium aluminum alcoholate nanowire of this example is carried out by the following steps:

[0034] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0035] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0036] Finally, 100 mg of Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 70 °C for 24 h to obtain magnesium aluminum alcoholate nanowires.

[0037] The morphology of the sample under scanning electron microscope is as follows Figure 1 The results show that when the Mg-Al-Li alloy is heated at 70°C for 24 hours, a large number of nano-sized needle-shaped magnesium aluminum alcoholates with high aspect ratio are generated on the surface. This high aspect ratio needle-shaped nanowire can well enhance the mechanical properties of the material.

[0038] Comparative Example 1: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0039] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0040] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0041] Finally, 100 mg of the Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 70 °C for 21 h to obtain magnesium aluminum alcoholate.

[0042] The morphology of the sample under scanning electron microscope is as follows Figure 2 The results show that when the Mg-Al-Li alloy is heated at 70℃ for 21h, a slightly larger number of nano-needle-shaped magnesium-aluminum alcoholates with shorter length are generated on the surface, and the reaction time is slightly short, which means it is still in the growth stage.

[0043] Comparative Example 2: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0044] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0045] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0046] Finally, 100 mg of Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 70 °C for 18 h to obtain magnesium aluminum alcoholate.

[0047] The morphology of the sample under scanning electron microscope is as follows Figure 3 The results show that Mg-Al-Li alloy reacts under constant temperature heating at 70℃ for 18h, and sparse and short nano-needle-shaped magnesium-aluminum alcoholates are generated on the surface. The reaction time is short and it is in the initial stage.

[0048] Comparative Example 3: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0049] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0050] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0051] Finally, 100 mg of the Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 70 °C for 15 h to obtain magnesium aluminum alcoholate.

[0052] The morphology of the sample under scanning electron microscope is as follows Figure 4 The results show that when the Mg-Al-Li alloy is heated at 70°C for 15 hours, a small amount of magnesium aluminum alcoholate nanoparticles are generated near the surface grain boundary, but nano-sized needle-shaped magnesium aluminum alcoholate has not yet been formed. It can be seen that the heating time has a great influence on the formation of nanowires.

[0053] Comparative Example 4: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0054] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0055] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0056] Finally, 100 mg of Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 60 °C for 18 h to obtain magnesium aluminum alcoholate.

[0057] The morphology of the sample under scanning electron microscope is as follows Figure 5 The results show that when the Mg-Al-Li alloy is heated at 60°C for 18 hours, a small amount of porous magnesium-aluminum alcoholate is formed on the surface. This porous magnesium-aluminum alcoholate has open porosity, fast transportation, better solvent flow and excellent electrical conductivity.

[0058] Comparative Example 5: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0059] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0060] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0061] Finally, 100 mg of Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 60° C. for 24 h to obtain magnesium aluminum alcoholate.

[0062] The morphology of the sample under scanning electron microscope is as follows Figure 6 The results show that when the Mg-Al-Li alloy is heated at 60°C for 24 hours, a slightly larger number of porous magnesium-aluminum alcoholates are formed on the surface.

[0063] Comparative Example 6: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0064] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0065] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0066] Finally, 100 mg of the Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 80 °C for 18 h to obtain magnesium aluminum alcoholate.

[0067] The morphology of the sample under scanning electron microscope is as follows Figure 7 The results show that when the Mg-Al-Li alloy is heated at 80℃ for 18h, a large amount of magnesium aluminum alcoholate nanoparticles are formed on the surface.

[0068] Comparative Example 7: The preparation method of a magnesium aluminum alcoholate in this comparative example is carried out according to the following steps:

[0069] First, the Mg-Al-Li alloy was cut into blocks of 20 mm × 20 mm × 10 mm, and then the surface was ground and polished;

[0070] Secondly, molecular sieves were added to anhydrous isopropanol and heated at 70 °C for one day to remove trace water;

[0071] Finally, 100 mg of the Mg-Al-Li alloy block was added into 20 mL of anhydrous isopropanol and heated at 80 °C for 24 h to obtain magnesium aluminum alcoholate.

[0072] The morphology of the sample under scanning electron microscope is as follows Figure 8 The results show that there is an optimal reaction temperature between the alloy and the alcohol. If the temperature is too high, the microstructure will be very fluffy and the aspect ratio will be smaller. If the temperature is too low, the tendency to form nanowires will be reduced. Therefore, both high and low temperatures are not conducive to the formation of nanowires.

[0073] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing magnesium aluminum alcoholate nanowires, characterized in that: Follow these steps: The Mg-Al-Li alloy was cut into blocks, added into anhydrous isopropanol, and heated at a constant temperature of 70°C for 24 hours to obtain magnesium aluminum alcoholate nanowires. The mass ratio of Mg, Al, and Li in the Mg-Al-Li alloy was 8:1:1, the volume ratio of the mass of the Mg-Al-Li alloy to the anhydrous isopropanol was ≤5 mg / ml, and the size of the Mg-Al-Li alloy block was 20 mm×20 mm×10 mm.

2. The method according to claim 1, characterized in that Anhydrous isopropanol was treated by adding molecular sieves and heating at 60-80°C to remove traces of water.

3. The method according to claim 2, characterized in that Molecular sieves were added to anhydrous isopropanol and heated at 60-80°C for one day.

4. The method according to claim 1, characterized in that: The Mg-Al-Li alloy block was polished and then added into anhydrous isopropanol.